Internet Censorship in Turkey: Stop Legalized Cyber-Murder - Bulut, Eduard Alan (Information World, 2009)
Banning or eliminating the websites is a “sheer cyber-murder”, which resembles to the case with Galileo. As his ideas contradicted with the authorities, he was sentenced to imprisonment for life, which is more or less the same with recent banning and elimination attempts. In a way, the current situation is the contemporary version of medieval experience. Without questioning on whether they are true or wrong according to “our” mind, it should be remembered that there are people with these ideas and preferences. Otherwise, there comes out the infringement of human rights, right to think, right to communicate. It is necessary to take action against the ongoing “intervention to preferences, thoughts, and fundamental human rights” and against the existing legalized “cyber-murder”.